The Effects of a Yearlong Recess Intervention on Body Fat Shifts in Elementary-Aged Children - Farbo, David J.; Rhea, Deborah J. (International Journal of Child Health and Nutrition, 2022)
Introduction: Obesity has continued to rise in recent years due to a lack of physical activity. The school environment contributes to this problem as opportunities for physical activity are eliminated for more classroom time. Recess, defined as unstructured, outdoor play, can increase MVPA and improve current obesity trends. This study aimed to examine body fat category shift differences in children who received 40-60 minutes and those who received 30 minutes. A secondary purpose was to examine differences by district, sex, grade, and race across both groups since they received more than the national average for recess. Methods: Students in 2nd-5th grade (7-11 years old) (N=393) were selected from schools serving as an intervention (N=190) or control school (N=203) in a larger longitudinal intervention titled Let’s Inspire Innovation N’ Kids (LiiNK). Bio-electrical impedance analysis was used to categorize students as either underfat, healthy, overfat, or obese. These categories were then used to determine if students shifted a category between pre and post-measurements. Results: At least 30 minutes of recess was significantly associated with a body fat shift in 2nd graders and females. Additionally, the percentage of obese students did not change over the school year. There was no association between the group, sex, or race. Conclusion: Due to this study occurring during COVID-19, it is hard to make definitive conclusions on the effects of increased recess time on obesity. However, some positive trends are pointing towards recess as a successful method of preventing a rise in childhood obesity.